Assessment of off-label prescribing: profile, evidence and evolution - Encarnación Blanco-Reina; Azucena Muñoz-García; Medical Research Centre (CIMES); Ricardo Ocaña-Riola; José Ramón del Prado-Llergo (Elsevier, 2017)
Objectives: The objectives of the study were to describe the extent and profile of off-label prescriptions, to evaluate the level of evidence supporting these indications, to assess the research activity in these conditions, and to determine to what extent these were authorized as new indications five years after the application. Methods: A cross-sectional study including all applications conducted in the Hospital Universitario Reina Sofía in Córdoba during 2010. Analysis: level of evidence according to the criteria by SIGN-NICE (Scottish Intercollegiate Guidelines Network, National Institute for Health and Care Excellence) and CEBM (Centre for Evidence-based Medicine), registered clinical trials (source: ClinicalTrials.gov), and review of product specifications and monthly newsletters from the Spanish Agency of Medicines and Medical Devices. Results: There were 190 applications for off-label prescription for 82 different indications. The most requested medications were: tacrolimus, mycophenolate, colistimethate and everolimus; the immunosuppressant group had the highest number of uses for non-approved indications. Out of the applications, 52.4% were based on some clinical trial, while the rest had a low level of evidence (observational studies and case reports). We have found on-going clinical trials for 67% of the indications, but new indications in their product specifications have only been authorized for nine drugs (bevacizumab, deferasirox, everolimus, lenalidomide, methotreate, sildenafil, sorafenib, raltegravir and tenofovir). Conclusions: We have detected a major volume of off-label prescription without good supporting evidence, which identifies these indications and medications as interesting research lines, but that require follow-up in terms of effectiveness and costs.